The Effects of Capital Expenditures, Human Development Index (HDI), and Economic Growth on Poverty in Regencies and Cities of East Nusa Tenggara for the 2013–2023 Period - Ni Putu Yunia Sukma Dewi (Journal of Development Economic and Social Studies, 2026)
This study aims to explore the relationship between total capital expenditure and the dynamics of the Human Development Index, economic growth rate, and poverty level at the district/city level in East Nusa Tenggara during the period 2013 to 2023. The information analyzed is sourced from panel secondary data compiled through official publications from the Central Bureau of Statistics and the Ministry of Finance. The approach used in the analysis process is path analysis utilizing SmartPLS. The results indicate that capital expenditure significantly influences economic growth and reduces poverty, but does not influence the HDI. Additionally, both the HDI and economic growth are shown to significantly and negatively influence poverty rates. Other findings revealed that capital expenditure influences poverty through economic growth. The findings suggest that while the allocation of capital expenditure is effective in stimulating the economy and reducing poverty rates, its contribution to human development has not yet reached an optimal level. Therefore, more targeted policy formulation and equitable budget distribution are needed to support inclusive and sustainable development in East Nusa Tenggara Province.